Comprehensive diagnostics of training of young fighters at the initial stage of preparation - Podlivaev, B. A.; Korzhenevsky, A. N. (International Journal of Wrestling Science, 2020)
The concept of the training system for highly qualified athletes, and the methodology for constructing model characteristics of the strongest athletes in the main groups of sports, was created by A.A. Novikov and his numerous students (Novikov, 2008; Podlivaev & Shakhmuradov, 2013), which was based on the concept of "model characteristics of the strongest athletes", and presently forms the basis of complex control in elite sports and is still extremely relevant. A comprehensive assessment of the state of various sides of fitness: technical, physical and functional gives complete information about the state of fitness of young combatants, contributes to the timely correction of training based on identifying the strengths and weaknesses of training and significantly increases the effectiveness of the training process. Evaluation of only individual sides of readiness and, in particular, physical qualities, significantly reduces the effectiveness of management of the training of young athletes (Graevskaya & Dolmatova, 2004; Kiselev, 2006; Korzhenevsky, 2011; Podlivaev, 2018; Podlivaev, 2016; Shakhmuradov, 2011).